Hydrogen influence on gallium arsenide thin films prepared by rf-magnetron sputtering technique - Vilcarromero, J. (2006)
We investigate the effect of the hydrogen intentional incorporation on the structural properties of the amorphous gallium arsenide prepared by rf-magnetron sputtering technique. The properties of the non-hydrogenated films are: band gap of 1.4 eV (E-04), Urbach energy of 110 meV, stoichiometric composition ([As]/[Ga] = 0.50), and dark conductivity of about 3.2 x 10(-5) (Omega.cm)(-1). Hydrogen was incorporated in the films by the introduction of an electronically controlled H-2 flux during deposition, keeping constant the other deposition parameters. It was observed that small hydrogen incorporation produces a great change in the structural properties of the films. The main changes result from the formation of GaAs nanocrystals with mean sizes of about 7 nm into the amorphous network.